The Influence of Profitability, Leverage, Liquidity, Company Size, and Audit Committee on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) in 2016-2020 - Intan Solaikhah; Eny Kusumawati (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
A company that develops properly will have an impact on the income and the tax of company. Companies with high income, the tax rate will be higher which will result in tax avoidance. The purpose of this study was to analyze the influence of of proftability, leverage, liquidity, firm size, and audit committee on tax avoidance. The population in this study are manufacturing companies listed on the Indonesia Stock Ecchange (IDX) during the 2016-2020. The sample was determined by purposive sampling technique and obtained a sample of 300 companies. This research uses statistikal analysis by regression analysis. The results in this study are profitability, leverage, liquidity, firm size and audit committee had affect the tax avoidance. Meanwhille firm size had no effect on tax avoidance.